2007
DOI: 10.1177/1352458506070446
|View full text |Cite
|
Sign up to set email alerts
|

I nterferon beta-1a slows progression of brain atrophy in relapsing-remitting multiple sclerosis predominantly by reducing gray matter atrophy

Abstract: Over a three-year period, treatment with IFN beta-1a significantly slowed the progression of whole-brain and GM atrophy, and of T1-hypointense LV accumulation, when compared with the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 58 publications
6
82
0
Order By: Relevance
“…[23][24][25][26]43 Despite these known effects of treatment with intramuscular interferon ␤-1a, both patients with SDP and those with stable MS exhibited loss of brain tissue during the course of this study. The extent of atrophy in untreated patients with MS is likely to be greater than that observed in the treated patients in this study, though it is not known whether the differential pattern of WM and GM atrophy would be as evident.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26]43 Despite these known effects of treatment with intramuscular interferon ␤-1a, both patients with SDP and those with stable MS exhibited loss of brain tissue during the course of this study. The extent of atrophy in untreated patients with MS is likely to be greater than that observed in the treated patients in this study, though it is not known whether the differential pattern of WM and GM atrophy would be as evident.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with those in previous studies that have suggested differential patterns of GM and WM atrophy during 2 years for patients with MS versus healthy controls 6 and that the rate of GM, but not WM, atrophy increased with advancing disease stage and was correlated with disability. 4,5,12,24,25 Fundamentally cross-sectional approaches like SIENAX are still widely used to measure GM and WM changes, 25 leading to potentially less accurate results and more analysis failures. Direct measures of cortical, GM, and WM volume changes with advantages similar to those of SIENA have been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…132,144 Future studies will undoubtedly explore the regional topography of such treatment effects as the relative effect on GM versus WM. 145 Atrophy measures are being incorporated into studies that explore the efficacy and safety of novel MS therapies. New data have emerged from natalizumab, 146 autologous hematopoietic stem cell transplantation, 147,148 and testosterone.…”
Section: Brain Atrophymentioning
confidence: 99%
“…One study suggests a benefit of interferon beta-1a (Avonex) in slowing the rate of gray matter atrophy, detectable at 2 and 3 years after initiating treatment [80]. Another recent study found that gray matter loss was detected in patients treated with interferon-β but not in untreated or Copaxone-treated patients assessed over a 2-year period using a voxel-based morphometry approach [81].…”
Section: Fig 1 Serial Cerebral Magnetic Resonance (Mr) Images Demonmentioning
confidence: 99%